Gut Microbes and Hepatic Encephalopathy: From the Old Concepts to New Perspectives - Rocco, Alba; Sgamato, Costantino; Compare, Debora; Coccoli, Pietro; Nardone, Olga Maria; Nardone, Gerardo (Frontiers in Cell and Developmental Biology, 2021)
Hepatic encephalopathy (HE) is a severe complication of advanced liver disease and acute liver failure. The clinical spectrum ranges from minor cognitive dysfunctions to lethargy, depressed consciousness, and coma and significantly impact the quality of life, morbidity, and mortality of the patients. It is commonly accepted that the gut milieu is essential for the development of HE; however, despite intensive research efforts, the pathogenesis Of HE is still not fully elucidated. As our knowledge of gut microbiota moves from the pioneering era of culture-dependent studies, the connection between microbes, inflammation, and metabolic pathways in the pathogenesis of HE is becoming increasingly clear, providing exciting therapeutic perspectives. This review will critically examine the latest research findings on the role of gut microbes in the pathophysiological pathways underlying HE. Moreover, currently available therapeutic options and novel treatment strategies are discussed.